Immunogenicity and safety of primary and booster vaccination with 2 investigational formulations of diphtheria, tetanus and Haemophilus influenzae type b antigens in a hexavalent DTPa-HBV-IPV/Hib combination vaccine in comparison with the licensed Infanrix hexa. Issue 7 (3rd July 2017) - Vesikari, Timo; Rivera, Luis; Korhonen, Tiina; Ahonen, Anitta; Cheuvart, Brigitte; Hezareh, Marjan; Janssens, Winnie; Mesaros, Narcisa
ABSTRACT: Safety and immunogenicity of 2 investigational formulations of diphtheria, tetanus and Haemophilus influenzae type b antigens of the combined diphtheria-tetanus-acellular pertussis-hepatitis B-inactivated poliomyelitis-Hib vaccine (DTPa-HBV-IPV/Hib) were evaluated in a Primary (NCT01248884) and a Booster vaccination (NCT01453998) study. In the Primary study, 721 healthy infants (randomized 1:1:1) received 3 doses of DTPa-HBV-IPV/Hib formulation A (DA TA Pa-HBV-IPV/Hib), or B (DB TB Pa-HBV-IPV/Hib) or the licensed DTPa-HBV-IPV/Hib vaccine ( Infanrix hexa, GSK; control group) at 2, 3, 4 months of age. Infants were planned to receive a booster dose at 12–15 months of age with the same formulation received in the Primary study; however, following high incidence of fever associated with the investigational formulations in the Primary study, the Booster study protocol was amended and all infants yet to receive a booster dose (N = 385) received the licensed vaccine. In the Primary study, non-inferiority of 3-dose vaccination with investigational formulations compared with the licensed vaccine was not demonstrated due to anti-pertactin failing to meet the non-inferiority criterion. Post-primary vaccination, most infants had seroprotective levels of anti-diphtheria (100% of infants), anti-tetanus antigens (100%), against hepatitis B (≥ 97.5% across groups), polyribosyl-ribitol-phosphate (≥ 88.0%) and poliovirus types 1–3 (≥ 90.5%). Seropositivity rates for each pertussis antigen were 100% in all groups. Higher incidence of fever (> 38°C) was reported in infants receiving the investigational formulations (Primary study: 75.0% [A] and 72.1% [B] vs 58.8% [control]; Booster study, before amendment: 49.4% and 46.6% vs 37.4%, respectively). The development of the investigational formulations was not further pursued.